(untitled) (Journal of Geography and Environmental Management, 2016)
In article are considered the main anthropogenic factors that determine the spatial distribution and dynamics of the negative processes of morphogenesis within the platform-denudation plains of Central Kazakhstan, characterized by an arid – climate conditions